Return to work after ischemic stroke in young adults: A registry-based follow-up study. (13th November 2018) - Aarnio, Karoliina; Rodríguez-Pardo, Jorge; Siegerink, Bob; Hardt, Juliane; Broman, Jenna; Tulkki, Lauri; Haapaniemi, Elena; Kaste, Markku; Tatlisumak, Turgut; Putaala, Jukka
Abstract : Objective: We aimed to investigate the proportion of young patients not returning to work (NRTW) at 1 year after ischemic stroke (IS) and during follow-up, and clinical factors associated with NRTW. Methods: Patients from the Helsinki Young Stroke Registry with an IS occurring in the years 1994–2007, who were at paid employment within 1 year before IS, and with NIH Stroke Scale score ⩽15 points at hospital discharge, were included. Data on periods of payment came from the Finnish Centre for Pensions, and death data from Statistics Finland. Multivariate logistic regression analyses assessed factors associated with NRTW 1 year after IS, and lasagna plots visualized the proportion of patients returning to work over time. Results: We included a total of 769 patients, of whom 289 (37.6%) were not working at 1 year, 323 (42.0%) at 2 years, and 361 (46.9%) at 5 years from IS. When adjusted for age, sex, socioeconomic status, and NIH Stroke Scale score at admission, factors associated with NRTW at 1 year after IS were large anterior strokes, strokes caused by large artery atherosclerosis, high-risk sources of cardioembolism, and rare causes other than dissection compared with undetermined cause, moderate to severe aphasia vs no aphasia, mild and moderate to severe limb paresis vs no paresis, and moderate to severe visual field deficit vs no deficit. Conclusions: NRTW is a frequent adverse outcome after IS in young adults with mild to moderate IS. Clinical variables available during acute hospitalization may allow prediction of NRTW.